Examining the relationship between the accreditation of engineering programmes and institutional performance: findings from the Gulf Cooperation Countries - Al Busaidi, Humaid (2021)
Little research has been undertaken to examine Engineering Programme Accreditation (EPA) and Institutional Performance (IP). Identified research gaps include the lack of studies examining EPA and the IP dimensions under investigation in general, and in the Higher Education Institutions (HEIs) of the Gulf Cooperation Countries (GCC) in particular. The aim of this research is to examine the relationship between EPA and the IP using six dimensions: graduate employability, graduation rate, retention and attrition, attracting academic staff and students, faculty staff research outputs, and university ranking. This quantitative research uses a survey-questionnaire of management and academic staff perceptions in GCC HEIs. Factor analysis is used to test if items may be summarised into a smaller set of factors. In order to test the relationship between EPA and the dimensions of IP using linear regression, a sample size of 211 responses from 15 GCC HEIs was used. The results of the hypotheses are surprising, showing that adopting EPA has a statistically significant positive relationship with all the dimensions of IP. The main survey findings are supplemented by a survey of unaccredited engineering programmes and a qualitative semi-structured interviews. The findings of this research contribute to the growing body of knowledge in the field of accreditation by determining the usefulness of adopting accreditation for engineering programmes with respect to its contribution to improving IP. Adopting engineering accreditation is linked to better job opportunities for graduates, improved rates of on-time graduation, improved retention and attrition rates, enhanced academic staff research outputs and improved university positions in ranking tables. In terms of the practical and contextual contributions, this study provides evidence to encourage decision makers to continue accrediting all engineering programmes in GCC HEIs, and invites consideration of how other academic programmes may access the benefits that accredited engineering programmes have enjoyed.